Approximating exponential and logarithmic functions using polynomial interpolation. Issue 3 (3rd April 2017) - Gordon, Sheldon P.; Yang, Yajun
ABSTRACT: This article takes a closer look at the problem of approximating the exponential and logarithmic functions using polynomials. Either as an alternative to or a precursor to Taylor polynomial approximations at the precalculus level, interpolating polynomials are considered. A measure of error is given and the behaviour of the error function is analysed. The results of interpolating polynomials are compared with those of Taylor polynomials.